IMPLEMENTATION OF THE PROPHET’S HADITHS ON HALAL LIFESTYLE: Analysis of Community Behavior at Bukit Mas Residence, Banyuwangi with the Living Hadith Approach - Amelia Damayanti (Riwayah: Jurnal Studi Hadis, 2024)
This research was conducted based on the author’s anxiety regarding the lifestyle circulating in society. Lifestyle in a society is increasingly diverse and only aims to fulfill trends has an impact on low awareness, especially in Muslim communities in choosing halal and haram. This research used a qualitative research method with a type of field research. This aims to find out what lifestyle people adopt in the Bukit Mas Residence, Banyuwangi district, East Java. Whether the community has implemented a halal lifestyle following the hadiths of the Prophet or not. The research results show that the halal lifestyle in the economic aspect that is implemented by the community is how they avoid usury or riba practice by using Shari’a Banking. In the aspect of halal food and beverages, the implementation of a halal lifestyle is carried out by avoiding haram food and beverages such as not buying products carelessly outside, studying halal certificates and or logos on the products, seeking information regarding the ingredients used and the beliefs or religion of the business owner. In the aspect of fashion, implementing the right dress according to the Shari’a as written in the Qur’an and hadith, such as covering the genitals, not exaggerating, and wearing appropriate clothes. The meaning of implementing a halal lifestyle is divided into two, namely in the background categories are religious ideology and reflection of previous lifestyles. Meanwhile, in the goal category is physical and spiritual health and improving the quality of life.